TRANSFORMASI HUNIAN DENGAN PERSPEKTIF SPASIAL DAN TATANAN BUDAYA: KOMPARASI PERMUKIMAN KUMUH BANG BUA, THAILAND DAN KAMPUNG NAGA, INDONESIA - Mega Sesotyaningtyas; Wiwik Dwi Pratiwi; Jawoto Sih Setyono (Department of Urban and Regional Planning, Diponegoro University, 2015)
The change of cultural order within the community living in slum area of Bang Bua, Thailand and that of indigenous settlement of Kampung Naga, Indonesia has transformed the built environment. This research focused on the settlement transformation and was done in Bang Bua in 2010 and in Kampung Naga in 2014. The research applies qualitative methods combined with gathering spatial that are related to spatial composition of the settlement. The research adapts the concept of cultural order theory developed by Habraken (1998). It is found that the transformation of settlement can been viewed from cultural order perspective. It is indicated that the change in thinking framework, community behavior, and the consensuses among community member have contributed the transformation. They are also connected and embedded with the space where the people live. © 2015 GJGP UNDIP. All rights reserved